Production of drum-dried jackfruit (Artocarpus heterophyllus) powder with different concentration of soy lecithin and gum arabic - Pua, Chun Kiat; Sheikh Abdul Hamid, Nazimah; Rahmat Ali, Gulam Rusul; Abdul Rahman, Rakmi (Elsevier, 2007)
The aim of the present study was to determine the optimum concentration of soy lecithin and gum arabic in producing drum-dried jackfruit (Artocarpus heterophyllus) powder using response surface methodology (RSM). Jackfruit puree was dried using a double drum drier set at 1 rpm, drum clearance of 0.01 in., and steam pressure of 2.3 bar. Soy lecithin and gum arabic were incorporated into jackfruit puree at different concentrations ranged from 1% to 5% and 5% to 15%, respectively. Soy lecithin and gum arabic were significant factors (at 95% confidence level) for moisture content, bulk density, Hunter L, a, b values and hedonic test during drum drying of jackfruit. A second-order polynomial model was found for each of the significant response. The jackfruit puree formulation to produce a good quality powder could be obtained by incorporating 2.65% of soy lecithin and 10.28% of gum arabic into the jackfruit puree (40% v/w water).